Do Immigrants Reduce Natives' Wages? Evidence from Germany - Thomas Bauer (Rutgers University, Department of Economics, 1998)
This paper investigates the effects of immigration on the wages of native workers in Germany. The analysis differentiates native and foreign workers according to their occupational status. The estimation of a translog production using 1990 cross section data reveals mixed results regarding the production relationship between different native and foreign groups. However, the effects of immigration on the wages of natives are numerically very small. Separability tests show that the use of an aggregate index for foreign labor and the treatment of natives and foreigners as similar inputs is not appropriate.
Keywords: J23; J61; 330; immigration; separability; substitutability; wages